The effects of Aglaia loheri BLANCO, Aleurites moluccana LINN. and Ardisia pyramidalis (CAVS.) PERS. plant extracts on hepatic histology and lipid peroxidation activity in carbon tetrachloride-treated mice. - Catap, Elena S. (Transactions of the National Academy of Science and Technology, 2011)
Three plant species Aglaia loheri, Aleurites moluccana. and Ardisia pyramidalis were evaluated for the antioxidant properties by employing lipid peroxidation assays and histological analysis in carbon tetrachloride (CCls)-treated mice. Sixty mice were divided into six treatment groups: 1) PBS-injected mice; 2) corn oil injected mice; 3) 30% CCl4 in corn oil intraperitoneally injected in mice every 7 hrs; 4) A. loheri extract + CCl4; 5) A. moluccana + CCl4; 6) A. pyramidalis + CCl4. Each of the plant extract was injected intraperitoneally on a daily basis. After two weeks, liver tissues were dissected out and subjected to lipid peroxidation assays. Liver samples were also processed for histopathological examination. Lipid peroxidation in both control groups was significantly lower than in CCl4-treated mice. Malondialdehyde (MDA) levels in Ardisia-treated and Aleurites-treated mice are higher than the CCl4-treated mice but the Aglaia-treated mice had lower MDA levels than the CCl4-treated mice. However, the difference was not statistically significant. In the histological examination, the extracts from Ardisia and Aleurites seemed to induce cellular regeneration in CCl4-treated mice. Higher degree of vacuolization and nuclear pyknosis, ballooning degeneration and multifocal necrosis were prominent in CCl4-treated liver tissues. Based on these results, it is recommended that further studies to confirm the antioxidant capacity of these plant species should employ varying extract dosages and longer treatment periods.